To Analyze and Study the Buying Behaviour of Women Among the Gen Z and Millennials in Chennai - Chordia, D Samithi (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The trend of online shopping has dramatically increased in the years since the internet's birth, which has given us a plethora of additional opportunities and made everything readily available. As we can see, a sizeable percentage of internet users are from Gen Z, Millennials, and other technologically advanced age groups. Both age groups appear to have a lot of influence and draw customers away from other purchases. The Millennial generation is the one who switched from traditional to online buying. Gen Z, on the other hand, was born during the era of the internet, thus everything was simple for them to utilise. For the study a sample size of 112 women respondents of the age group 18-41 years were taken through random sampling technique. How to cite this article: Chordia DS. To Analyze and Study the Buying Behaviour of Women Among the Gen Z and Millennials in Chennai. J Adv Res Jrnl Mass Comm 2023; 10(2): 32-36. DOI: https://doi.org/10.24321/2395.3810.2023013